Study of the G-ratio of aluminium silicon carbide nano particles reinforced metal matrix composites. Issue 1 (October 2020) - Nandakumar, A.; Rajmohan, T.; Sundararajan, R.; Venkatesh, K.; Muni Deepak, N.; Venkateshwaran, K.
Abstract: Grinding plays an essential role in obtaining high dimensional accuracy and surface finish. Three types of work pieces were used with different ratios of SiC (1%, 2%, 3%). When the composition of SiC increases, the G-ratio decreases. This type of material is highly used in aerospace applications due to its low density and good wear and corrosion resistance. It is genuinely believed that Al-SiC has tremendous potential for application in the aerospace industry. A critical role is played by grinding in achieving good surface finish and improved dimensional accuracy. Therefore, a strategy to improve the grinding rate and surface finish is important for economic production. In this research, the various grinding ratio was found out and results show that G-ratio is high when coolant is used and G-ratio is low when coolant is not used.